PROBLEMS OF FOREIGN STUDENTS OF TURKIC ORIGIN AND SOLUTION PROPOSALS - İlknur ÖZPINAR; Arzu AYDOĞAN YENMEZ; Seher MANDACI ŞAHİN (International Journal of Eurasia Social Sciences, 2017)
Especially in recentyears, it is began to seen that Turkey become to a more effective position in the field of economic, social and cultural field in the World and our country is among the priority countries in which students from different countries want to study where it is particularly relevant in terms of history and culture. However, reading in a foreign country undoubtedly brings with it some difficulties. In order for the students to benefit from the educational opportunities in Turkey at the highest level, studies should be carried out to identify and eliminate the problems they have experienced. In this direction, this study aims to examine the reasons for students’ preferring Turkey and to determine the difficulties encountered that Turkish native foreign students who come to education faculties for higher education. The research, which was carried out by adopting qualitative research approach, was carried out with 18 students studying at Ömer Halisdemir University Faculty of Education. The research data were collected by a questionnaire form and semi-structured interviews. At the end of the research, it has been revealed that most of the students were satisfied with the program and they make their living by working. The main reasons to prefer Turkey for higher education are; more qualified education, liking and curiosity of Turkey, the possibility of having a good job and cultural similarities. It is also obtained from this study that economic problems are the most common problems faced by many students. In this direction, it is suggested to increase the scholarship opportunities for students who want to study with their own possibilities.